La vénus d’ille, by prosper mérimée: an exotic element in the creation of the fantastic narrative - Borges, Maria do Carmo Faustino (Lettres Françaises, 2017)
La Vénus d’Ille, a short story by Prosper Mérimée, is the study object of an approach of the Fantastic Literature. This paper focuses on the supernatural, an element which consolidates this narrative and its theme: a Venus statue, a character from the Greek-Roman culture, is introduced in the life of the citizens of Ille in the 19th century, establishing the mystery in the dialogic relation between the real world and the reality of what we imagine. In this sense, unusual events take place permeated by strangeness, doubt, and ambiguity, making possible for the reader to question the given social values. The theoretical basis of this study includes Tzvetan Todorov, Irène Bessière, Antoine Faivre, Louis Vax, and Jean Molino, with the purpose of observing the fantastic construction of the animated statue and the real world as well as the motives to reach a central subject, the marriage. This paper concludes that the fantastic genre is not committed to answers or explanations for events. It is a play on words created in the fictional universe. Therefore, it is not linked to reason, but it is inside the real world with the aim here to denounce the mistakes of capitalism.